Konfliktnost med mladostniki in starši - Čotar Konrad, Sonja (Psihološka obzorja (Ljubljana), 2012)
Despite the growing number of studies on family conflict abroad this issue still remains relatively unexplored in Slovenia. The importance of this issue is also evident from the increasing incidence of aggressive behaviour in family disputes in the Slovenian society. This represents new challenges science is faced with daily. Firstly, this paper tries to define the concept of family dispute and to separate it from other related concepts. Secondly, we provide a valuable theoretical and empirical understanding of reasons that determine conflict in the family, and more specifically the conflict between adolescents and their parents. The article critically points out the psychological and developmental aspect of the conflict between adolescents and their parents, where four possible developmental psychological perspectives and interpretations of conflicts in family are confronted and evaluated: the psychoanalytic perspective, the socio-biological, the cognitive developmental and the sociorelational aspects. Finally, the article tries to illuminate conflict in family as an element of change of the entire family system through the prism of family coping with stress adopting the Burr-Klein model (1994) and to evaluate the model on the basis of a hypothetically presented case of family functioning.
Keywords: konflikti; družinski odnosi; mladostniki; starši; razvojna psihologija; developmental psychology